Elaboração, aplicação e análise de um programa de ensino de inglês a partir de uma análise de erros - Maestrello, Ana Paula Vedovato (2006)
The theorical perspective of behavior analysis contributes with education when it considers student´s and/or teacher´s behaviors, as well as conditions of teaching, making statements in order to make learning more satisfactory. One of these contributions is the Personal System of Instruction (PSI) idealized by Fred S. Keller (1974). The aim of this research was the elaboration, application and analysis of an English teaching programm meant for children studying in public school as an extra-course activity foccused on the students mistakes during the evaluations throughout the course. The research was divided in three steps: 1st) the application of two tests throughout the period when teaching was conventional; 2nd) the transition between the conventional and the proposal of an individualized teaching; at this time a third test, an analysis of the mistakes happened in the previous evaluations and planning and application of remediative procedures introducting some principles of programmed teaching occured; 3rd) the application of the final three evaluations already under a new perspective from the first three previous, and the utilization of individualized exercises as a teaching initial condition. The results proved that teaching may be more effective and faster when the proposal of individualization is established as a teaching condition